2011
DOI: 10.1021/jf104845j
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Modification of a Model Homogalacturonan with the Thermally Tolerant Pectin Methylesterase from Citrus: 1. Nanostructural Characterization, Enzyme Mode of Action, and Effect of pH

Abstract: Methyl ester distribution in pectin homogalacturonan has a major influence on functionality. Enzymatic engineering of the pectin nanostructure for tailoring functionality can expand the role of pectin as a food-formulating agent and the use of in situ modification in prepared foods. We report on the mode of action of a unique citrus thermally tolerant pectin methylesterase (TT-PME) and the nanostructural modifications that it produces. The enzyme was used to produce a controlled demethylesterification series f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…Depending on regulatory factors such as pH, ion availability, methyl esterification state of the substrate and potentially intrinsic differences in mode of action of the respective isoforms, PME activity leads to a multitude of different methyl esterification patterns (Cameron et al 2008;Cameron et al 2011;Catoire et al 1998;Denes et al 2000;Willats et al 2001). These patterns, or epitopes, differ both in terms of mechanical properties and degradability, which makes it difficult to transfer in vitro findings to the in vivo situation.…”
mentioning
confidence: 99%
“…Depending on regulatory factors such as pH, ion availability, methyl esterification state of the substrate and potentially intrinsic differences in mode of action of the respective isoforms, PME activity leads to a multitude of different methyl esterification patterns (Cameron et al 2008;Cameron et al 2011;Catoire et al 1998;Denes et al 2000;Willats et al 2001). These patterns, or epitopes, differ both in terms of mechanical properties and degradability, which makes it difficult to transfer in vitro findings to the in vivo situation.…”
mentioning
confidence: 99%
“…For example, alkaline pectinases (which comprise polygalacturonases, pectin lyases, pectate lyases, and pectin esterases) have found many industrial applications, such as bioscouring of cotton, oil extraction, treatment of industrial wastewater, and papermaking [76][77][78]. The reactions of many specific pectic enzymes have been well studied, e.g., pectin methylesterase [79][80][81][82], polygalacturonase [83,84], and pectin lyase [85,86]. Studies with proteases have shown the importance of proteinaceous moiety in emulsifying properties of pectin [87,88].…”
Section: Pectinmentioning
confidence: 99%
“…Pectin's functionality is mostly related to its net charge and the distribution of charge along the largely linear homogalacturonan (HG) regions of the molecules. The structural complexity of pectin is well established (Caffall & Mohnen, 2009;Coenen, Bakx, Verhoef, Schols, & Voragen, 2007;Ridley, O'Neill, & Mohnen, 2001;Willats, Knox, & Mikkelsen, 2006) and necessitates a statistical approach for describing a population of pectin molecules and its two major regions, i.e., homogalacturonan and rhamnogalacturonan I (Cameron, Luzio, Goodner, & Williams, 2008;Cameron, Luzio, Vasu, Savary, & Williams, 2011;Daas, Voragen, & Schols, 2001;Guillotin et al, 2005;Kim et al, 2013;Kim et al, 2014;Ralet et al, 2012;Remoroza, Buchholt, Gruppen, & Schols, 2014;Williams, Cucheval, Nasseri, & Ralet, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 66 Arabidopsis PMEs included 73% were alkaline, 23% acidic and 4% neutral. Modes of action for several plant PMEs with alkaline pIs and one with an acidic pI have been studied (Cameron et al, 2008;Cameron et al, 2011;Catoire, Pierron, Morvan, Herve du Penhoat, & Goldberg, 1998;Denes, Baron, Renard, Pean, & Drilleau, 2000;Duvetter et al, 2006;Kim, Teng, & Wicker, 2005;Kim et al, 2013;Kim et al, 2014). These enzymes have been shown to remove methyl esters in a progressive fashion, producing blocks of contiguous non methylesterified GalAs and an ordered distribution of charge, at least at neutral reaction pHs and after a minimum number of contiguous GalAs have been demethylesterified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation